2002
DOI: 10.1046/j.1365-2109.2002.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of pea seed meal in diets for gilthead sea bream (Sparus aurata ) juveniles

Abstract: Juvenile gilthead sea bream with a mean initial body weight of 5 g were fed for 12 weeks with experimental diets containing 10% and 20% fishmeal protein (sole protein source in the control diet) replaced by processed pea seed meals. The processed pea seed meals were dehulled, defibred, extruded and microground pea seed meal (PSM1) or whole pea treated by infrared radiation and ground (PSM2). Apparent digestibility coefficients of the experimental diets were determined in a separate trial. At the end of the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
7
34
0
3
Order By: Relevance
“…Considering the growth trend of treatment groups in the present study, it can be deducted that more effective results could have been obtained when the experiment would have continued after 45 days of trial, which also could be a one of the reasons for the lower utilization of CGM in this study compared to those in the previous ones. Overall, our results in terms of growth performance and feed utilization data of sea bream fed increasing levels of CGM are comparable to those of previous studies on sea bream nutrition (Robaina et al, 1997;Fournier et al, 2002;Pereira and Oliva-Teles, 2003;Pereira and Oliva-Teles, 2002;De Francesco et al, 2007).…”
Section: Resultssupporting
confidence: 93%
“…Considering the growth trend of treatment groups in the present study, it can be deducted that more effective results could have been obtained when the experiment would have continued after 45 days of trial, which also could be a one of the reasons for the lower utilization of CGM in this study compared to those in the previous ones. Overall, our results in terms of growth performance and feed utilization data of sea bream fed increasing levels of CGM are comparable to those of previous studies on sea bream nutrition (Robaina et al, 1997;Fournier et al, 2002;Pereira and Oliva-Teles, 2003;Pereira and Oliva-Teles, 2002;De Francesco et al, 2007).…”
Section: Resultssupporting
confidence: 93%
“…Gilthead seabream in the current study showed no negative effects on carcass composition or HSI of either low (PL) or high (PH) P containing diets compared to the control. Processed pea seed meals at similar inclusion levels were tested in gilthead seabream diets (Pereira & Oliva‐Teles 2002), and the authors demonstrated that no significant differences occurred in carcass proximate composition and HSI. Equivalent results were also found for European seabass juveniles fed pea seed meal diets (Gouveia & Davies 1998, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers of Mediterranean species are focused on the use of plant meals (Robaina et al1995, Watanabe et al 1998, Aoki et al 2000, Kissil et al 2000, Pereira and Oliva-Teles 2002, Gómez-Requeni et al 2004, Hernández et al 2007, Sánchez-Lozano et al 2007). However, plant meals yield lower protein levels and present other problems that limit their use in diets.…”
Section: Introductionmentioning
confidence: 99%